Audit Sistem Infomasi Pelayanan Pasien pada RSUD Waikabubak Menggunakan Cobit Framework 4.1 - Roslin Roiki Woda; Andreas Ariyanto Rangga; Maria Wilda Malo (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
The objective of Waikabubak Regional Hospital's information system deployment is to streamline the administrative procedure. Information system performance must be measured or audited to ascertain its maturity in order to give information technology a positive role and to ensure that it operates in line with the hospital's planning and business objectives. Information system audits conducted with the COBIT 4.1 Framework are highly beneficial to management, auditors, and users alike. Determining the information system's maturity level at Waikabubak Regional Hospital is the goal of this study. The ability to offer suggestions that can be used as raw material for future information system improvements is another goal of this research. The study's findings display the system maturity level score. From a total of 20 sudomains, the information gathered at Waikabubak Regional Hospital is 3 or at level Defined Process; only 6 of these indicated a score of level 2 maturity level (Repeatable but Intuitive), which is provided as a recommendation.. Keywords: Expert System, Epilepsy, Certainty Factor